STRATEGI KOMUNIKASI PEMBELAJARAN DAN PENGARUHNYA TERHADAP KUALITAS BELAJAR SISWA DI MASA PANDEMI - Labib, Hunaidah (Magister Manajemen Universitas Islam Malang, 2022)
AbstactThe study aims to identify and find out (1) learning strategies that best used at the secondary education level during the pandemic (2) factors that influence the learning quality and (3) correlation and significance of communication in learning.Fatigue, boredom and passivity lead to students' less attention and focus during the learning process. Online-based learning has reduced active communication between teachers and students who, some of them, might just be listeners or just access the digital-based learning media without watching the video presentation. The situation challenges teachers to be more creative in identifying the best strategy to ensure good quality of learning.The study used the survey method and quantitative description. 5 percent out of total 100 students were done with random sampling. Observation and questionnaire distribution are instruments of data collection. The data was later analized using product-moment correlation (rxy) test and significance test with k-2 degree of freedom 78.The study concludes that there are correlation and significance between teachers' communication strategy and students' learning quality with the t-count result 10,3284 more than the t-table result 1,66462 and based on the KD test, iy was found that a value of 57,76% means that there is a contribution of variable X and Variable Y while 42,24 is influenced by other factors. Â Keywords: Strategy, Learning Communication, Learning Quality, Influence of Teachers' Communication on learning.